Efektivitas E-modul Getaran dalam Kehidupan Sehari-Hari pada Pembelajaran Daring Untuk Meningkatkan Keterampilan Proses Sains Siswa - Aditya Fahlevi; Asrizal Asrizal (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2021)
Physics learning has a central role in developing the 21st century skills that learners must achieve. Physics aksis one of science learning can cultivate and develop 21st century skills through science literacy and science process skills. Science process skills can be trained in the learning of physics through processes in conducting scientific activities and scientific attitudes. But from the initial studies conducted, it was found that the ability of the student's science process in online learning has artistic variety of problems. One alternative to problem solving is to use electronic modules (e-modules) designed to improve students' science process skills in online learning. The methodology used in this study was a quasi-experiment with the design of theÃÂ posttestÃÂ only control research design group. The aim of the study was to determine the effectiveness of the use of e-modules of vibration in everyday life on online learning to improve the science process skills of grade X high school students.ÃÂ TheÃÂ effectiveness of e-module use is determined by analyzing the science process skills of experimental classroom and control classes. The significance of the effectiveness of the use of e-modules on aspects of knowledge and skills of the science process is analyzed by tests of normality, homogeneity and t tests. From the analysis of data obtained by the results of the study, the use of vibrational e-modules in everyday life in online learning is effective to improve students' knowledge and skills of the science process.